Antifilarial Activity of Eucalyptus globulus Labill. Leaves Against Brugia malayi (Bangladesh Pharmaceutical Journal, 2016)
The present study is aimed to evaluate the antifilarial activity of Eucalyptus globules Labill. (Myrtaceae) against human lymphatic filarial parasite Brugia malayi in vitro and in vivo. The ethanolic extract of the leaves was tested in vitro on adult worms and microfilariae (mf) of B. malayi and the active sample was further evaluated in vivo in B. malayi intraperitoneally (i.p.) transplanted in the jird model (Meriones unguiculatus) and Mastomys coucha subcutaneously infected with infective larvae (L3). The ethanolic extract of the leaves of the E. globulus was tested in vitro on adult worms and microfilariae (mf) of B. malayi and the active sample was further evaluated in vivo in B. malayi. The ethanolic extract was active in vitro (IC50: adult = 62.5 ?g/ml; mf = 31.2. ?g/ml) where it demonstrated 66.7% adulticidal and embryostatic effect on B. malayi in Mastomys at a dose of 5 × 100 mg/kg by oral route. The antifilarial test conducted was at 5 × 100 mg/kg by subcutaneous route revealed excellent adulticidal efficacy resulting in to the death of 66.7% transplanted adult B. malayi in the peritoneal cavity of jirds in addition to noticeable microfilaricidal action on the day of autopsy. The findings revealed that the extract from the leaves of E. globulus contains promising in vitro and in vivo antifilarial activity against human lymphatic filarial parasite B. malayi which may be further explored to new antifilarial agents.Bangladesh Pharmaceutical Journal 19(1): 44-47, 2016